2012
DOI: 10.4103/1947-2714.97214
|View full text |Cite
|
Sign up to set email alerts
|

Peroral extrusion of the peritoneal catheter in an infant

Abstract: Peroral extrusion of the distal end of a ventriculo-peritoneal shunt tube is the potentially hazardous end result of a bowel perforation with only few case reports in the literature. The distal end of the peritoneal catheter got fractured in a 4-year-old child and it protruded out through the mouth. The cranial incision was opened and the shunt divided below the chamber. The ventricular end and the chamber and distal end were removed through this incision. In the present successfully managed case we review the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…All the n = 46 manuscripts included for systematic review are full-text articles[ 17 - 62 ]. Thirty-five manuscripts described/detailed the isolated case[ 17 , 19 , 23 - 30 , 32 , 33 , 37 - 43 , 45 , 46 , 48 - 54 , 56 - 62 ]. Two of the manuscripts included in the review are original articles[ 35 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the n = 46 manuscripts included for systematic review are full-text articles[ 17 - 62 ]. Thirty-five manuscripts described/detailed the isolated case[ 17 , 19 , 23 - 30 , 32 , 33 , 37 - 43 , 45 , 46 , 48 - 54 , 56 - 62 ]. Two of the manuscripts included in the review are original articles[ 35 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The functional status of the VPS catheter was not mentioned/not provided in the literature reviewed for n = 22 of Group A and n = 11 of Group B cases[ 17 , 19 - 23 , 26 , 27 , 30 - 32 , 34 - 36 , 41 - 49 , 51 - 54 , 57 - 62 ]. The distal end of the VPS catheter was draining CSF, confirming that the VPS catheter was functioning well in n = 6 of Group A and n = 2 of Group B cases, respectively[ 18 , 24 , 25 , 29 , 37 , 39 , 50 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous reports, recommendations for fasting after treatment vary greatly, mostly between 2 and 4 days. [ 1 9 10 13 16 21 ] In two cases, fasting lasted until 7 to 14 days. [ 5 18 ] All the literatures reported that no abdominal problems occurred posttreatment.…”
Section: Discussionmentioning
confidence: 99%
“…chemical reactions occurs between the functional groups on the dye and adsorbent surfaces; then, low reversibility of adsorption occurs. Therefore, different surface characteristics would help to explain the reversibility of adsorption [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. As the regenerated adsorbent illustrated satisfactory adsorption-desorption capability towards methyl orange dye, it can thus be reused as potential adsorbent for wastewater treatment.…”
Section: Desorption Of Dye and Reuse Of Adsorbentmentioning
confidence: 99%